Dynamic demand adjustment and exchange rate volatility - Vesna Corbo (Sveriges Riksbank, 2014)
A common finding in the international-economics literature is that the elasticity of substitution between domestically produced and imported goods is smaller in the short than in the long run. Despite this, most of today's commonly used macroeconomic models assume this elasticity to be constant. This paper studies the implications of relaxing the assumption that the elasticity is constant over time horizons, through the modeling of habit formation. Compared to the standard model without habits, the proposed dynamic demand model exhibits substantially more volatile exchange rates and can generate higher real exchange rate persistence in the presence of interest rate smoothing. A high volatility of the exchange rate turns out to be optimal in this model and is hence not an artefact of the assumed monetary policy rule. Moreover, the dynamic demand model outperforms the standard model in terms of matching moments in data for a number of other variables.
Keywords: E21; E52; F31; F41; F44; 330; Elasticities; Exchange Rates; Habit Formation; Optimal Monetary Policy